Accounting Students’ Perceptions : Anticipatory Socialization, Professional Commitment, and Moral Intensity Regrading Whistleblowing Intentions - Rizka Destiana; Mellisa Dhea Savitri (Journal of Social Research, 2025)
The purpose of this research is to provide accounting students with a thorough conceptual framework for internal whistleblowing, which will subsequently be empirically validated. In order to achieve this goal, the study looks at the moderating effect of moral intensity perception and the mediating role of professional commitment in relation to anticipatory socialization's impact on the inclination to report infractions. The study's target demographic consists of accounting majors who plan to graduate in 2024. A survey that is self-administered is given to 186 accounting students. To evaluate the suggested hypotheses, route analysis and moderation regression analysis are also used. The results of the hypothesis test show that the following relationships exist: moral intensity positively influences whistleblowing intention, moral intensity negatively moderates the relationship between professional commitment and whistleblowing intention, and moral intensity does not moderate the mediating effect of anticipatory socialization on whistleblowing intention. Positive relationships are found between anticipatory socialization and professional commitment, professional commitment and whistleblowing intention, and professional commitment and professional socialization. The aforementioned results highlight the significance of incorporating ethical education into undergraduate courses and educating students about the ethical principles, goals, and societal duties of the accounting profession.